STRATEGI DAN HAMBATAN MIGRAN AFGANISTAN BERADAPTASI DI KOTA MAKASSAR - Ahdiyanti, Istika (Pascasarjana IAIN Sorong, 2023)
This study aims to identify and analyze 1. the adaptation strategies of Afghan refugees while in Makassar City 2. to analyze the barriers for Afghan refugees to adapt to Makassar City . This research was conducted at Pondok Nugraha, jl. Daeng tata, Blok 4F No.88, kel, Bonto Duri. Tamalate district, Makassar South Sulawesi. The method used in this study is a qualitative method, purposive sampling technique using a case study approach and interviewing 16 informants. The results show that in the adaptation strategy of Afghan refugees, refugees develop a strategy into three stages of adaptation strategies, the first strategy in the social field at the social stage of refugees divides it into two stages of strategy, namely the initial strategy including finding refugees from Afghanistan and conducting socialization later in the stage second is the refugee development strategy to formulate strategies that include: Joining in mingling with activities that occur in the refugee environment and in the community, and promoting tolerance. At the cultural stage, Afghan refugees formulate a strategy by adopting and following several local culture. Whereas at the economic stage the refugees have a strategy by forming a relationship through mutually beneficial relationships with one another. In terms of adaptation barriers, refugees experience several obstacles among refugees that are difficult to adapt due to differences in language, discriminated treatment by society, and many differences in culture.